HUBUNGAN STATUS KEK IBU HAMIL DAN BBLR DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS TAWIRI KOTA AMBON - Nilfar Ruaida; Octovina Soumokil (Poltekkes Kemenkes Maluku, 2018)
Stunting in infants is influenced by maternal nutritional histories such as chronic energy deficiency (CED) and iron deficiency anemia. Maternal nutritional status before and during pregnancy affect thegrowth of the fetus. The purpose of this study was to determine the relationship between CED status ofpregnant women with the incidence of stunting in children under five in the Tawiri health center inAmbon City. This research type was an observational with case-control design and using purposivesampling. The research subjects were children who had stunting with 76 cases and 163 controls.Univariate data analysis using frequency distribution, bivariate using Chi-square. The results showedthat pregnant women with CED, their children did not experience stunting (77.91%). LBW occurs inpregnant women who experience CED (70.00%), while LBW does not occur in pregnant women whoare not CED at 71.77%. Stunting occur in infants who are not LBW (64.47%). Stunting did not occurin infants with a history of no LBW (98.16%). Keywords: CED status, pregnant women, LBW, stunting